Design of automatic rotor blades folding system using NiTi shape memory alloy actuator - Ali, M. I. F.; Abdullah, E. J. (Institute of Physics Publishing, 2016)
This present paper will study the requirements for development of a new Automatic Rotor Blades Folding (ARBF) system that could possibly solve the availability, compatibility and complexity issue of upgrading a manual to a fully automatic rotor blades folding system of a helicopter. As a subject matter, the Royal Malaysian Navy Super Lynx Mk 100 was chosen as the baseline model. The aim of the study was to propose a design of SMART ARBF's Shape Memory Alloy (SMA) actuator and proof of operating concept using a developed scale down prototype model. The performance target for the full folding sequence is less than ten minutes. Further analysis on design requirements was carried out, which consisted of three main phases. Phase 1 was studying the SMA behavior on the Nickel Titanium (NiTi) SMA wire and spring (extension type). Technical values like activation requirement, contraction length, and stroke- power and stroke-temperature relationship were gathered. Phase 2 was the development of the prototype where the proposed design of stepped-retractable SMA actuator was introduced. A complete model of the SMART ARBF system that consisted of a base, a main rotor hub, four main rotor blades, four SMA actuators and also electrical wiring connections was fabricated and assembled. Phase 3 was test and analysis whereby a PINENG-PN968s-10000mAh Power Bank's 5 volts, which was reduced to 2.5 volts using LM2596 Step-Down Converter, powered and activated the NiTi spring inside each actuator. The bias spring (compression type), which functions to protract and push the blades to spread position, will compress together with the retraction of actuators and pull the blades to the folding position. Once the power was removed and SMA spring deactivated, the bias spring stiffness will extend the SMA spring and casing and push the blades back to spread position. The timing for the whole revolution was recorded. Based on the experimental analysis, the recorded timing for folding sequence is 2.5 minutes in average and therefore met the required criteria.